2006
DOI: 10.1590/s0036-46652006000400013
|View full text |Cite
|
Sign up to set email alerts
|

Unpredicted HTLV-1 infection in female sex worker from Imbituba, Santa Catarina, Brazil

Abstract: Dear Sir, Recently, some of us presented data concerning HIV frequency in female sex workers (FSW) from the port city of Imbituba, Santa Catarina (SC), Southern Brazil 10 . Out of 90 FSW, six (6.7%) were found to be HIV-positive, and significant association were found between HIV infection and the number of clients attended per day (p = 0.008), and sexual relations without frequent use of condoms (p = 0.015). Now, in order to add some information concerning to other human retroviruses (human T-lymphotropic vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…There are approximately 1.5 million people of Japanese descent in Brazil and most of them living in São Paulo state [17]. The prevalence of 5.1% (95% CI: 4.2-6.0) of HTLV-1 infection found in this study is higher than those observed in other studies conducted in different regions of the country considering HTLV-1 endemic a ´reas, including Salvador, the city with the highest HTLV-1 prevalence (1.48%) in Brazil [28][29][30][31], and higher than those conducted among specific risk groups, such as men who have sex with men, people who used illicit drugs, HIV-infected persons, and commercial sex workers, with prevalence rates varying from 0.7% to 3.0% [32][33][34][35]. This high rate (5.1%) found in the present study is similar to that observed in previous study involving Japanese community of Campo Grande, Mato Grosso do Sul State (6.8%) [13] probably because the majority of subjects in both studies was descendant of Okinawans as well as of people from other HTLV-1-endemic regions in Japan.…”
Section: Discussionmentioning
confidence: 54%
“…There are approximately 1.5 million people of Japanese descent in Brazil and most of them living in São Paulo state [17]. The prevalence of 5.1% (95% CI: 4.2-6.0) of HTLV-1 infection found in this study is higher than those observed in other studies conducted in different regions of the country considering HTLV-1 endemic a ´reas, including Salvador, the city with the highest HTLV-1 prevalence (1.48%) in Brazil [28][29][30][31], and higher than those conducted among specific risk groups, such as men who have sex with men, people who used illicit drugs, HIV-infected persons, and commercial sex workers, with prevalence rates varying from 0.7% to 3.0% [32][33][34][35]. This high rate (5.1%) found in the present study is similar to that observed in previous study involving Japanese community of Campo Grande, Mato Grosso do Sul State (6.8%) [13] probably because the majority of subjects in both studies was descendant of Okinawans as well as of people from other HTLV-1-endemic regions in Japan.…”
Section: Discussionmentioning
confidence: 54%
“…It was conducted by our group, analyzing 90 female sex workers from the same geographical region of this study. One HTLV-1-positive pregnant woman was detected, and she was advised not to breastfeed her offspring 16 .…”
Section: Discussionmentioning
confidence: 99%
“…There are approximately 1.5 million people of Japanese descent in Brazil and most of them living in São Paulo state [17]. The prevalence of 5.1% (95% CI: 4.2-6.0) of HTLV-1 infection found in this study is higher than those observed in other studies conducted in different regions of the country considering HTLV-1 endemic a ´reas, including Salvador, the city with the highest HTLV-1 prevalence (1.48%) in Brazil [28][29][30][31], and higher than those conducted among specific risk groups, such as men who have sex with men, people who used illicit drugs, HIV-infected persons, and commercial sex workers, with prevalence rates varying from 0.7% to 3.0% [32][33][34][35]. This high rate (5.1%) found in the present study is similar to that observed in previous study involving Japanese community of Campo Grande, Mato Grosso do Sul State (6.8%) [13] probably because the majority of subjects in both studies was descendant of Okinawans as well as of people from other HTLV-1-endemic regions in Japan.…”
Section: Discussionmentioning
confidence: 54%